Representasi Psikologis Toleransi Beragama Dalam Kehidupan Komunitas Hindu-Muslim Di Senduro Lumajang - Robi'atur Rohmah; Naurah Alyani (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2026)
This study investigates the psychological representations of interreligious tolerance within the Hindu-Muslim community in Senduro District, Lumajang Regency, Indonesia. The region was selected due to its unique harmony amidst religious diversity and demographic disparity. A descriptive qualitative approach with a phenomenological method was employed to uncover the subjective meanings of tolerance from both individual and communal experiences. Data were collected through naturalistic observation, semi-structured in-depth interviews, and documentation. Findings reveal that Silo Gending Site functions as a symbolic space respected by both religious groups. Daily interactions, such as: community service, interfaith celebrations, and interreligious marriages reflect emotional bonds and prosocial behaviors. Tolerance is understood through expressions like “harmony,” “considering each other’s feelings,” and “not disturbing one another.” Key driving factors include the culture of mutual cooperation and a long-standing history of peaceful coexistence, while external influences such as negative media narratives pose challenges. The study concludes that religious tolerance encompasses cognitive, affective, and conative dimensions rooted in daily social practices. This research contributes to the advancement of cross-cultural social psychology and offers a grounded model of interfaith harmony in multicultural societies.